Le droit à l’avortement : révélateur et activateur de pratiques parlementaires au Royaume-UniAbortion rights: revealing and activating parliamentary practices in the United Kingdom - Alexandrine Guyard-Nedelec (Revue LISA)
The implementation of a strategy that could be described as “erosion”, but also the defence, liberalisation and decriminalisation of abortion rights all play out in the legislative field. How are the UK regulatory and procedural constraints dealt with in this debate? The article first analyses a number of amendments relating to abortion rights, highlighting the role of the executive, the discursive framework in which debates take place, etc. Then, it looks at the interplay of scales triggered by this issue. The most striking example is that of the decriminalisation of abortion in Northern Ireland by the Westminster Parliament in the summer of 2019, in the face of the political deadlock preventing any decision at Stormont. In such unprecedented situations, the UK Supreme Court, although not part of parliamentary practices strictly speaking, has a significant role to play, as do the European Convention on Human Rights and the United Nations. A cluster of multiple actors emerges, who interact within a cluster of political considerations. A game of inter-national alliances sets up in which the local Assemblies, Westminster and Downing Street seem to triangulate. The conclusion highlights the growing role of the judiciary and the fundamental rights turn, which may suggest that courts more than parliaments will shape developments in abortion rights in the years to come.